PENERAPAN LKPD PADA MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR DAN HASIL BELAJAR MATEMATIKA SISWA SMA - Ainur Rosyidah (Polynom: Journal in Mathematics Education, 2023)
This study aims to see the development of student learning outcomes and student activeness in participating in learning Mathematics with Discovery Learning strategies assisted by LKPD. This research went through four stages, namely planning, implementation, observation, and reflection. The subjects of this study were students of class XI F7 SMAN 4 Yogyakarta in the academic year 2023/2024 which amounted to 36 male students. Data analysis is by describing the data obtained from the results of the implementation of the action. Data collection techniques used in this study were observation and tests. The data analysis used is the analysis of student learning activeness data, test results and teacher observation data. Based on the results of research and data analysis, it can be concluded that the application of the Discovery Learning learning model can improve the activeness and learning outcomes of mathematics students in class XI F7 SMAN 4 Yogyakarta in the 2023/2024 school year. The results showed an increase in cycle I by 4 students and cycle II by 15 students. This is in line with the increase in student learning outcomes in cycle I and cycle II. Cycle I showed student learning outcomes of 77.78% and cycle II of 91.67%. These learning outcomes increased by 13.89%. This research is expected to be a reference for other researchers for further research related to increasing student learning activeness and student learning outcomes.